Ethanolic Extract of Fermented Houttuynia cordata Thunb Induces Human Leukemic HL-60 and Molt-4 Cell Apoptosis Via Oxidative Stress and a Mitochondrial Pathway - Banjerdpongchai R. (2014)
Houttuynia cordata Thunb (HCT) is a medicinal plant of the Saururaceae family which features antimutagenic and antiviral properties. For extraction, the whole plants were fermented or non-fermented with yeast and ethanol then the whole plants were dried, ground and extracted with 95% ethanol or water. The aims of this study were to compare cytotoxic effects, apoptosis induction, and mechanism(s) with the ethanolic and water extracts of fermented and non-fermented HCT. Cytotoxicity was assessed using the MTT assay in human leukemic HL-60, Molt-4 and peripheral blood mononuclear cells (PBMCs). Apoptotic death was characterized by staining with propidium iodide and examined under a fluorescence microscope. Peroxide radical production and reduction of mitochondrial transmembrane potential (MTP) were determined using 2',7'-dichlorohydrofluorescein diacetate and 3,3'-dihexyloxacarbocyanine iodide and flow cytometry, respectively. The expression of caspase-9 was identified by immunoblotting. The ethanolic extract of fermented HCT was cytotoxic to HL-60 > Molt-4 > PBMCs, to a greater extent than the non-fermented preparation and the number of apoptotic cells was higher. The alcoholic (fermented) extract produced more radicals than the non-fermented in HL-60 cells but the converse was observed in Molt-4 cells. Reduction of MTP was found in HL-60 and Molt-4 cells treated with the alcoholic (fermented) extract and caspase-9 was cleaved dose-dependently in both cells. In conclusion, the alcoholic extract of fermented HCT was more toxic to human leukemic cells than the non-fermented and both cell lines underwent apoptosis via oxidative stress and a mitochondrial pathway.